The Journey of Human Life in Islamic Perspective: Learning from the Spirit to the Hereafter - Agustina, Restika; Mahmud, Salami; Maulidia, Maulidia; Mahfud, Aris; Fadli, Fatmawati (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
In Islam, the journey of human life encompasses five main phases: the Realm of the Spirit, the Womb, Worldly Life, Barzakh, and the Hereafter. Each of these phases holds profound significance in understanding the human being as a moral and spiritual entity. This research aims to examine the human life journey from the realm of the soul to the afterlife from an Islamic perspective, and to explore the spiritual and moral values within each phase that are essential for character building and Islamic education. This study adopts a qualitative descriptive method through content analysis of the Qur’an, hadith, and relevant Islamic scholarly works. The findings reveal: (1) the Realm of the Spirit, where every soul testified to Allah’s oneness; (2) the Womb, the phase of physical development and the infusion of the soul; (3) Worldly Life, a temporary stage of trial, responsibility, and worship as Allah’s vicegerent; (4) Barzakh, the transitional stage between death and resurrection; and (5) the Hereafter, the eternal stage of reward or punishment based on one’s deeds. Each phase emphasizes key spiritual and moral responsibilities, which shape an individual’s character and deepen their religious consciousness. A holistic understanding of these stages encourages Muslims to live with purpose, striving for righteousness in this world while preparing for the ultimate goal eternal happiness in the Hereafter. This research contributes to the advancement of knowledge, particularly in the field of self-understanding within Islamic thought.